K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 2 2017

a) 16 - (x - 4 )= -10                                                                         b) 3- ( x +2) = -24

x -4 = 16 - ( -10 )                                                                                x -2 = 32 - (-24 )

x -4 = 26                                                                                            x -2 = 33

x = 26 +4                                                                                           x     =33 +2

x = 30                                                                                                x     = 35

11 tháng 6 2015

a) \(\left(3^5\times3^7\right):3^{10}+5\times2^4-7^3:7=3^{12}:3^{10}+5\times2^4-7^2\)

\(=3^2-5\times16-7^2=9-80-49=-120\)

b) \(15:\left(3^5:3^4\right)-2^9:2^7=15:3-2^2=5-4=1\)

c)\(5\times3^5:\left(3^8:3^5\right)-2^3\times5=5\times3^5:3^3-2^3\times5\)

\(=5\times3^2-2^3\times5=5\times9-8\times5=45-40=5\)

19 tháng 8 2016

Bài 1: 

a) (2^9 . 3 + 2^9 . 5) : 2^12

= [2^9 . (3 + 5)] : 2^12

= [2^9 . 8] : 2^12

= [2^9 . 2^3] : 2^12

= 2^12 : 2^12 

= 1

b) 13^2 - (5^2 . 4 + 2^2 . 15)

= 13^2 - (5^2 . 4 + 4 . 15)

= 13^2 - [4 . (5^2 + 15)]

= 13^2 - [4 . (25 + 15)]

= 13^2 - [4 . 40]

= 13^2 - 160

= 13^2 - 40^2

= -27^2

= 729

Bài 2:

a) 30 . (2^2 . 15 - x) = 30

             2^2 . 15 - x   = 30 : 30

             2^2 . 15 - x   = 1

             4 . 15            = 1 + x

                60               = 1 + x

=>             x  = 60 - 1

                 x   = 59

               

19 tháng 8 2016

Bài 2:

b) 2^4 . 38 - 2^4 . x = 16

    16 . (38 - x)          = 16

             38 - x           = 16 : 16

             38 - x           = 1

                     x           = 38 - 1

                     x           = 37

c) (7 . x - 11^3) = 2^5 . 5^2 + 200

    (7 . x - 11^3)  = 2^5 . 5^2 + 5^2 . 2^3

    (7 . x - 11^3)  = 5^2 . (2^5 + 2^3)

    (7 . x - 11^3)  = 25 . 40

    (7 . x - 1331)  = 1000

     7 . x               = 1000 + 1331

     7 . x               = 2331

          x               = 2331 : 7

          x               = 333.